Miri Resident Office / Norliza Othman - Othman, Norliza (University Technology MARA Sarawak, 2013)
Miri Resident Office is one of the main government office situated in the Northern Region of Sarawak. Miri Resident Office is responsible for the administration of Miri which is headed by the Resident. There are two district offices and a few subdistricts under the administration of Miri Resident Office. There are Miri District Office and Marudi District Office, which are headed by District Officer (D.O). The subdistricts are Long Lama Subdistrict, Niah Subdistrict, Sibuti Subdistrict. These offices are headed by an officer which is called Sarawak Administrative Officer or also known as SAO. Miri covers an area of 26,777 km2 and the population of Miri Division is around 396,000. Miri is neigbour to Brunei and Sabah on the north and has become one of the fast growing cities in Sarawak.